Cotton root and shoot growth as affected by application of mepiquat chloride to cotton seeds - doi: 10.4025/actasciagron.v34i1.12369 (Acta Scientiarum. Agronomy, 2011)
The effects of mepiquat chloride (MC) application to cotton seeds on the initial growth of the plant roots and shoots were studied in a greenhouse experiment. Glass-front containers with 27 L of soil were used in the experiment. Cotton seeds of the cultivar FM 993 were sprayed with MC at five different doses of active ingredient (a.i.): 0, 3, 6, 9 and 12 g kg-1 seed. The shoot and root dry matter, leaf area, shoot:root ratio, leaf area: root growth ratio, and shoot length were evaluated 21 days after sowing. The root growth was evaluated every three days up to 18 days. The application of MC to cotton seeds decreased the shoot length but had no significant effect on the dry matter production, root length, shoot:root ratio or leaf area: root length ratio. Thus, the application of MC to cotton seeds is not expected to have a deleterious effect on plant water acquisition.